Business Planning : D’Ace Jewellery Sdn Bhd / Ahmad Arif Azizan ...[et al.] - Azizan, Ahmad Arif; Bakarudin, Badrul Amin; Jalaludin, Mohd Faiz; Abdul Karim, Muhammad Ikram; Mohamed, Nur Suraya (2009)
Nowadays, there are many people that are involved in business. The majority businessmen in this country are Chinese peoples. So we want to show that Malay people can also successful businessman. After making a lot of research in this area we all had agreed to establish D’Ace Jewellery Sdn. Bhd. The nature of the business is a partnership company. D’Ace Jewellery Sdn. Bhd is a company that provides services to customers about a design and making jewelry product. Today, the request on jewelry product by metal or the other metarials are having good responses in market. This is one of the reasons why we ventured into this sector. The target areas are city center area, where there are a lot of school, college and residents The location of our business is in Bandar Machang, Kelantan. The commencement date of our business will be on the 1 of January 2009. The factors for us in selecting this business is the fact there is this kind of business are highly market nowadays in this area, the target market in this business is teenager, local citizen, vip and young adults who is the majority citizen in the area. Our main objective is to provide jewelry product according to customer need in designing their own jewelry design, so we build up this type of company to serving them. This business are attracting people with our specialty and exclusive in design in jewelry, by the way type of our services are different rather other business in this location